The Relationship Between Body Mass Index, Body Composition, And Motor Skills In Physical Education Students In The Basketball Branch: Literature Review - Tri Angriawan (Journal of Sport Education, Coaching, and Health (JOCCA), 2025)
This literature review examines the relationship between Body Mass Index (BMI), body composition, and motor skills among Physical Education students in basketball. The background of this study is based on the need to understand how anthropometric and physiological characteristics influence students’ basketball-related motor performance. The objective of this review was to synthesize conceptual and empirical evidence regarding the contribution of BMI, fat mass, and lean body mass to agility, speed, vertical jump, coordination, balance, and basketball-specific skills. This study used a literature review method by analyzing peer-reviewed articles published within the last ten years from Scopus- and SINTA-indexed journals. The findings indicate that BMI is useful as an initial screening indicator, but it is less accurate in explaining sport performance because it cannot distinguish fat mass from muscle mass. Empirically, students with normal BMI, lower body fat percentage, and higher lean body mass tend to demonstrate better agility, sprint ability, jumping performance, coordination, dribbling, passing, shooting, and defensive movement. Conversely, excessive fat mass increases mechanical load and reduces movement efficiency. It can be concluded that body composition is a stronger predictor of basketball motor skills than BMI alone. Therefore, basketball learning and training programs should integrate BMI assessment, body composition analysis, physical fitness testing, and sport-specific motor skill evaluation.